Maternal Death Following Medical Treatment of Paroxysmal Supraventricular Tachycardia in Late Gestation - Ping-Hung Kuo; Kung-Liahng Wang; Jen-Ruei Chen; Chih-Ping Chen; Jen-Jui Lin; Ming-Chao Huang; Hung-I Yeh (Elsevier, 2005)
Objective: We present an unusual case of maternal death following medical treatment of paroxysmal supraventricular tachycardia (PSVT) in late gestation. Case Report: A 30-year-old woman, gravida 1, para 0, came to the outpatient clinic of our obstetrics and gynecology department at 35 weeks of gestation. She had suffered from palpitation and shortness of breath that lasted 3 days. Electrocardiographic examination revealed PSVT. Although intravenous administration of verapamil (5 mg) and adenosine (36 mg) effectively prevented the relapse of PSVT, the patient lost consciousness 30 minutes after her last dose of adenosine with sudden-onset convulsions. Despite immediate administration of advanced cardiac life support, she showed no signs of improvement and died. Conclusion: PSVT in late gestation can be associated with maternal death even following conversion to sinus rhythm using medical treatment. Clinical use of adenosine for PSVT should alert the clinician to the potential risk of administering a high dose of adenosine to a pregnant woman, which can lead to maternal mortality in late gestation. Administration of a high dose of adenosine was, in our opinion, partially responsible for the maternal death and intrauterine fetal demise in this case.